Uso de serviços odontológicos em crianças de 12 anos de idade em Santa Maria, RS, Brasil - Fabro, Joana Possamai Del (2013)
BACKGROUND: Data about the interaction of different predictors for the use of dental services among representative samples of Brazilian children are scarce. Understanding the effect of psychosocial, clinical, sociodemographic, and context factors on inequalities in the use of oral health services provides important data for the implementation of measures to promote health. AIM: To assess the influence of socioeconomics and psychosocial factors and contextual covariates for use of dental services in 12-years old schoolchildren in Brazil. METHODS: An epidemiological survey was conducted in 12-years old schoolchildren in Santa Maria, Brazil. A two-stage cluster sampling was used. Data about the oral conditions were collected through clinical exams at school and contextual data related to the location of the school where the child studies were obtained through official publications of the municipality. Socioeconomic conditions were evaluated by a questionnaire answered by their parents. This questionnaire was used to assess whether the child had visited any dental care service in the previous 6 months and the reasons for dental visit (preventive/others than preventive). Psychosocial factors were collected by using the Brazilian version of Child Perceptions Questionnaire (CPQ 11-14). The study of association used multilevel models of Poisson regression analysis. RESULTS: The prevalence of use of dental services was 47.43%; 69.84% of the subjects used the dental services for preventive reasons. Participants from lower family income, those who rated their oral health as "fair / poor / very poor" and students of schools with low rates of approval were less to have gone to the dentist in the last six months. The reasons for dental services varied across socioeconomic groups. Moreover, those who perceived their oral health as "fair / poor / very poor", and those from schools with low approval rates were more likely to use dental services in an emergency / treatment. CONCLUSION: This study showed that psychosocial factors, and socioeconomic context are important predictors for the use of dental services, emphasizing the need for public intervention to consider the effect of social determinants in reducing inequities in use of services.